IMPROVING STUDENTS’ SPEAKING ACHIEVEMENT IN NARRATIVE TEXT BY USING PICTURE FOR THE ELEVENTH GRADE STUDENTS OF MAN KRECEK - mulki, alfan (LENTERA : Jurnal Pendidikan dan Pengajaran; Vol 8 No 2 (2018): LENTERA : Jurnal Pendidikan dan Pengajaran, 2018)
The difficulty in speaking is found among the students of MAN Krecek. This appears based on the observation about the problem of teaching speaking with the teacher and preliminary test of students of X IIB. Therefore, the researcher decides to use picture as media to improve their speaking. The design of study is collaborative classroom action research (CAR) which the researcher is assisted by a collaborator in conducting the research. The subject of this research is XI B of MAN Krecek. Total students of XI B are 40 students that consisted of 29 female and 11 male. The result of study indicated that the students are active and motivated after the teaching learning process. The students’ speaking achievement improved after being implemented by using picture. The improvement is shown by increasing the percentage of the students’ speaking achievement by using picture in speaking test and improving the activities of the students in the class. Based on the result of students’ speaking achievement after being implemented by using picture is improved, it is shown in cycle I is 30% of subject who classified into a success with the average is 70,60 (71) and in cycle II is 87,5% of subject who classified into a success with the average is 82,10.